The effect of obliging the defendant to show evidence against himself - Ameen Al-Jaf, Fwrat Rostam (Opción, 2020)
The study aims to investigate the effect of obliging the defendant to show evidence against himself via comparative qualitative research methods. As a result, the Iraqi legislator, in this article, dealt with the case of the court conviction that the book or the bond is in the possession of the opponent who is required to provide it. In conclusion, obliging the opponent to provide evidence against himself is an exception from the general origin which stipulates that it is not permissible for the opponent to provide evidence against himself.